Analisis Peranan Akuntansi Dan Pelaporan Lingkungan Pada Perusahaan PT Asia Pulp & Paper (APP) Sinar Mas - R.Pandin, Maria Yovita; Maharani Putri, Viviane; Daffa Setiawan, Farrel (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
In the business world, environmental accounting and reporting has become a major concern. Concern about environmental issues such as climate change, natural resource conservation, and sustainability has encouraged companies and organizations around the world to consider the environmental impact of their business operations. More and more companies are adopting sustainable business practices and committing to environmental responsibility. This research aims to provide benefits to manufacturing companies such as Asia Pulp & Paper Sinar Mas regarding the important role of environmental accounting and reporting for a company. The methodused in this researc his qualitative with a descriptive approach. The data usedare secondary data. The results of this research are on Asia Pulp & Paper Sinar Mas which has implemented and presented environmental reporting.